Maximizing Surgical Success by Aligning Interventions to Outcomes: A Systematic Review - Bonnie A. Armstrong, PhD; Arthur Tung, BSc; Lisha Lo, MPH; Spencer S. Abssy, BSc; Maham Zulfiqar, BSc; Juliette van Oost, BSc; Julie Wong, BSc; Josh Janevski, BSc; Julia Martyniuk, MI; Patricia Trbovich, PhD (Annals of Surgery Open)
Objective:. This study aimed to identify common intraoperative interventions in surgery and evaluate their effectiveness in improving surgical outcomes. Background:. Despite decades of efforts, surgical adverse events remain stubbornly high. There are concerns that too much responsibility is placed on individuals to create change (ie, person-based interventions) rather than adapting systems to support human performance (ie, system-based interventions). This focus may be due to our limited understanding of which interventions most effectively improve outcomes. Methods:. A 2-step search was conducted. Systematic and meta-analytic reviews of Medline, CINAHL, Embase, PsycINFO, Scopus, Cochrane Reviews, Cochrane Protocols and Cochrane Trials were identified, and individual studies within these reviews were selected. Qualitative content analysis categorized intervention and outcome types using inductive and deductive methods. Intervention details and directional findings for all outcomes were extracted. Results:. A total of 575 studies were included in the final analysis comprising 5,288,513 cases, 25,435 providers and patients, 2608 hospitals, across 50 countries, with 1221 outcomes extracted. Overall, the most common interventions were person-based, including education (38%) and policy (19%). Person-based interventions were more likely to improve interpersonal outcomes such as culture, professional development, and resilience. In contrast, system-based interventions, such as technology (15%), cognitive aids (11%), equipment (11%), standardization (4%), and environment redesign (2%), though less frequently implemented, were effective across all outcome types. Conclusions:. Although person-based interventions are widely implemented, system-based interventions generally have a greater impact on surgical outcomes. These results offer valuable insights for optimizing the alignment of interventions to outcomes.